Internet content regulation, public drug websites and the growth in hidden Internet services - Barratt, Monica; Lenton, Simon; Allen, M. (Taylor and Francis, 2013)
Governments have traditionally censored drug-related information, both in traditional media and, in recent years, in online media. We explore Internet content regulation from a drug-policy perspective by describing the likely impacts of censoring drug websites and the parallel growth in hidden Internet services. Australia proposes a compulsory Internet filtering regime that would block websites that ‘depict, express or otherwise deal with matters of… drug misuse or addiction’ and/or ‘promote, incite or instruct in matters of crime’. In this article, we present findings from a mixed-methods study of online drug discussion. Our research found that websites dealing with drugs, that would likely be blocked by the filter, in fact contributed positively to harm reduction. Such sites helped people access more comprehensive and relevant information than was available elsewhere. Blocking these websites would likely drive drug discussion underground at a time when corporate-controlled ‘walled gardens’ (e.g. Facebook) and proprietary operating systems on mobile devices may also limit open drug discussion. At the same time, hidden Internet services, such as Silk Road, have emerged that are not affected by Internet filtering. The inability for any government to regulate Tor websites and the crypto-currency Bitcoin poses a unique challenge to drug prohibition policies.